Pengendalian Getah Kuning Manggis Menggunakan Ekstrak Rumput Laut dan Pemupukan Kalium - I KETUT SUADA; NI WAYAN SUNITI (Fakultas Pertanian Universitas Udayana, 2015)
The Control of Mangosteen Yellow Latex Using Seaweed Extract and Potassium Fertilizer. The yellow latex disease decreases fruit quality of mangosteen because of exogenic latex causes dirty fruit and the endogenic latex makes the bitter fruit taste, then it does not deserve to be consumed. The causal agent of the disease was Verticillium alboatrum, Fusarium oxysporum, and Pestalotia macrotricha. Control using synthetic chemical for the fungus is severely decreasing the quality of the environment, therefore the use of organic agent such as botanical fungicide and the use of potassium fertilizer is recommended. The purpose of this research is to find the dose of potassium fertilizer and sea weed extract to decrease yellow latex disease of mangosteen fruit. The research was done in-vivo in the field with indicator of the decrease of yellow latex incident. The research showed that potassium fertilizer of 1.5 kg/plant combine with 1% extract was the best treatment with the lowest yellow latex incident of 9.4%. The treatment effective decreasing the disease of 56.3% compared to control and 56.9% when it is compared to 0,2% Antracol fungicide.